Pengaruh Perilaku Active Defending pada Bystander terhadap Pencegahan Bullying (Studi Kasus Siswa SMA di Kota Medan) - Mutiara Nabila Nst; Wilodati Wilodati Wilodati; Mirna Nur Alia Abdullah (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2023)
The issue of bullying has become a serious problem in the world of education. Whereas schools should be places of learning that are safe for students to improve their academic knowledge and social life. There are three central roles involved in bullying events, namely: perpetrator, victim, and eye witness or bystander. Active defending behavior is a type of bystander (witnesses) who takes the role of the victim to help when bullying occurs. The purpose of this study was to measure and determine the effect of active defending behavior on bystanders in preventing bullying among high school students. Explanative quantitative type approach with survey method will be used in this study. The results of this study show that the value of F = 0.730 and the value of Sig 0.849 > 0.05. Then, the results of the data analysis of the value of the coefficient of determination of the independent variable active defending is 0.64 so that it can be stated that active defending has an effect on preventing bullying in students by 6.4% while there are several other things that also affect prevention of bullying in students by 93.6% but not mentioned in the this research. It is hoped that this research can be used as a reference to reduce the problem of bullying in schools by intensifying preventive measures